Body Size, Age and Growth Pattern of the most represented anurans in Inselbergs of northeastern Argentina - Piñeiro, José Miguel (2023)
The decline of biodiversity is an urgent concern that raises significant alarm today. Several species vanish without their biology being understood, or sometimes, even without awareness of their existence. Due to the significance that the Inselbergs has to biodiversity and nature, as they have been recognized as genuine evolutionary laboratories, they present a unique opportunity to enhance our understanding of biologically unexplored species. Our study presents the first information regarding the body size, age and growth pattern of Scinax fuscovarius, Odontophrynus asper, and Melanophryniscus atroluteus, the three most frequently encountered anuran species in the Inselbergs outcrops of northeastern Argentina. We have demonstrated that the variations in body size cannot be attributed to the effect of the specific hill where the species inhabit. We discovered that sexual dimorphism in age and the analyzed morphological variables is expressed differently in the three examined species. We also demonstrated that the observed differences in body size between populations of M. atroluteus of Inselbergs and the Atlantic Forest of Argentina can be attributed to differences in age at sexual maturity and growth patterns. However, we believe that other proximate mechanisms should be taken into account, such as the effects of the environment and inter- and intra-specific competition experienced during the larval stages, for a better understanding of the population differences in adult body size and age. Our findings will assist in the evaluation of species management and conservation strategies within their habitat.